PENGARUH PEMBERIAN STIMULUS MUSICAL FRISSON TERHADAP PERFORMA MEMORI JANGKA PENDEK - Christopher Alvaro Dharmawan; Yosef Purwoko; Maria Belladonna Rahmawati; Hexanto Muhartomo (PERDOSNI, 2020)
Introduction: A person’s intelligence may be determined by the capacity of working and short-term memory. Stimulations restrain the early-onset neurodegenerative process and short-term memory loss. Musical frisson stimulation can increase the production of dopamine, blood flow, and activities of some parts of the brain that have roles in short-term memory process. Aims: To prove that musical frisson stimulation can increase short-term memory performance and association between the duration of frisson and short-term memory performance change. Methods: A quasi-experimental study with one group pre and post-test design was carried out among medical students of Diponegoro University. A total of 25 participants were selected by purposive sampling technique. The stimulation was by listening to mp3 of 5 researcher-selected songs that could induce frisson using an earphone before going to bed. Stimulation would last for 15 minutes in 3 consecutive days. The frisson that was felt measured by using a stopwatch in terms of minutes. Short-term memory was measured before and after the stimulation using Scenery Picture Memory Test (SPMT), so that the difference could be calculated. The collected data was then analyzed using Wilcoxon test and simple linear regression. Results: The pre-test score was 15.763.179, meanwhile the post-test score was 20 (13-23), so there was a significant increase on SPMT score (p < 0.001). Duration of the frisson had positive effect on SPMT score differences (p < 0.001). Discussion: Musical frisson stimulation can increase short-term memory performance. The frisson that lasts longer will have more significant improvement on short-term memory performance. Keywords: Duration, musical frisson, scenery picture memory test, short-term memory